New model of brittleness index to locate the sweet spots for hydraulic fracturing in unconventional reservoirs - Iqbal, O. (Asian Research Publishing Network, 2019)
Rock characterization in term of brittleness is necessary for successful stimulation of shale gas reservoirs. High brittleness is required to prevent healing of natural and induced hydraulic fractures and also to decrease the breakdown pressure for fracture initiation and propagation. Several definitions of brittleness and methods for its estimation has been reviewed in this study in order to come up with most applicable and promising conclusion. The brittleness in term of brittleness index (BI) can be quantified from laboratory on core samples, geophysical methods and from well logs. There are many limitations in lab-based estimation of BI on core samples but still consider benchmark for calibration with other methods. The estimation of brittleness from mineralogy and dynamic elastic parameters like Young's modulus, Poison's ratio is common in field application. The new model of brittleness index is proposed based on mineral contents and geomechanical properties, which could be used to classify rock into brittle and ductile layers. The importance of mechanical behavior in term of brittle and ductile in shale gas fracturing were also reviewed because shale with high brittleness index (BI) or brittle shale exist natural fractures that are closed before stimulation and can provide fracture network or avenues through stimulation. The brittle shale also has low breakdown pressure and no fracture healing as compared to ductile shale. The integration of laboratory and geophysical methods (determination of P and S waves from well logs) are recommended for accurate estimation of brittleness index (BI) for shale gas reservoirs. Â© 2006-2019 Asian Research Publishing Network (ARPN).